Recognition of foreign divorce Judgments in Peru - Monge-Talavera, Luz (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The extraterritorial effectiveness of foreign judgments is a matter of major importance in Private International Law. This paper presents the legal regime established in the Peruvian Law, making constant reference to its jurisprudential application in terms of recognition of foreign divorce decrees. Although legislative efforts aimed at simplifying the processing of the judicial process are verified, the norm analysis and its application by the jurisprudence reveal certain lags and contradictions that could endanger the principle of effective judicial protection.